POLYMORPHISMS OF THE IMMUNE RESPONSE GENES:SELECTED BIOLOGICAL, METHODICAL AND MEDICAL ASPECTS - Kubistova, Zuzana; Mrazek, Frantisek; Petrek, Martin (Biomedical papers, 2009)
Background: Variants of the immune response genes (IRG) are considered a potential source of interindividual differences in both innate and adaptive immune responses. A large number of gene polymorphisms have been reported as alternative forms of the IRG nucleotide sequence with important functional consequences for the structure/expression of immune response molecules. Accordingly, IRG polymorphisms are considered responsible for various monogenic diseases. They may also affect individual predisposition to complex diseases or modify their clinical course.Methods and Results: In this review we define IRG polymorphism including its potential functionality. Common approaches used for the investigation of IRG polymorphisms are next briefly described. We then review current approaches (including genome - wide studies) for assessing the importance of particular IRG variants in the susceptibility to and clinical course of complex diseases. Finally, based on our own experience and on the literature, we illustrate current knowledge of the genetic component of two selected complex diseases (sarcoidosis and coronary artery disease).Conclusions: Despite major advances in genotyping technology and general knowledge of the implications of IRG in the susceptibility to complex diseases, the potential clinical application of these approaches still faces major challenges.
Keywords: Immune response genes/Gene polymorphism/Susceptibility to diseases/Complex diseases